Improving The Quality Of Slum Settlements In Laut Dendang Village, Percut Sei Tuan District, Deli Serdang Regency - Misman; Wahyu Hidayat; Feby Milanie (Yayasan Multidimensi Kreatif, 2024)
The problem of slums is one of the main problems in urban development. This is quite controversial because there has been an actual effort to deal with slums along with the emergence and growth of new slums. The slums in Laut Dendang Village, Percut Sei Tuan District, Deli Serdang Regency will specifically instill a negative paradigm about government administration, portraying the government as powerless and incapable of regulating life and livelihood services for its citizens. People living in slums in Laut Dendang Village, Percut Sei Tuan District, Deli Serdang Regency, on the other hand, usually come from low-income groups, who are often responsible for disorder and violations of discipline in various social structures. Slums and housing problems in Laut Dendang Village, Percut Sei Tuan District, Deli Serdang Regency have developed into problems that need to be solved collectively through the mandate of the law.